Interview with Alexander Pavlov - Pavlov Alexander (Journal of Economic Sociology, 2018)
An interview with Alexander Pavlov, an expert at the Khamovniki Foundation and editor-in-chief of the news agency “Ulyanovsk — the Сity of News,” was conducted in February 2018 by Elena Gudova, a junior researcher at the Laboratory for Studies in Economic Sociology, Higher School of Economics. Alexander Pavlov talks about his unique experience of research in the construction industry at various levels of decision-making, from obtaining a land plot by a general contractor to buying property by the final owners. Until 2016, cooperation among stakeholders mostly relied on acquaintance and personal connections, while the mere square meter became the main currency. The construction industry functioned quite successfully, largely due to informal agreements and a lack of government presence up to the moment when the problem of defrauded co-investors emerged in political discourse. However, these investors were more likely to be legal entities involved in the redistribution of financial resources rather than potential tenants with mortgages. Attempts to make it all “like in Europe” disturb the existing structure and order, since the state’s main task in this sphere is the distribution of housing regardless of the real needs of population. Simultaneously, these needs have greatly changed from the 1950s rhetoric that “by the year 1980 everyone will get an apartment” towards the quality of housing. Ironically, quality was threatened due to the fact that only the construction teams had actual knowledge of what was happening at the construction areas. Alexander Pavlov’s ‘Saga of the Square Meter’ allows us to have another perspective of the construction industry, but it reveals many topics familiar to economic sociologists as well: a contradiction between informal economic practices and actions of the state; failures of high modernism; the importance of trust because of kidalovo or scam threats; the emergence of a symbolic order based on a new currency, and other subjects.